A Multidimensional Analysis of Nutritional Status, Eating Behavior, and Nutrient Intake among Female Students in the Humid Tropical Rainforest Region - Anshory, Jamil (Bachelor Nutrition Study Program - Faculty of Medicine, 2024)
Nutritional issues in Indonesia, particularly in the tropical rainforest regions of Kalimantan, remain a significant challenge, especially among female university students who are vulnerable to nutritional status disorders. This cross-sectional observational analytic study was conducted from June to July 2024 at Universitas Muhammadiyah Kalimantan Timur, involving 259 female students aged 19-20 years, selected through purposive sampling. Data were collected through anthropometric measurements, including Body Mass Index (BMI), Mid-Upper Arm Circumference (MUAC), and Waist-to-Hip Ratio (WHR). Dietary behavior data were obtained using a balanced nutrition behavior questionnaire, while dietary habits and nutrient intake were assessed using a Food Frequency Questionnaire (FFQ) analyzed with NutriSurvey software. Data collection was carried out by trained enumerators, and data analysis was conducted using IBM SPSS Statistics version 26, encompassing descriptive analysis as well as bivariate and multivariate tests to evaluate inter-variable relationships. The results indicated that 59.7% of respondents had a normal nutritional status based on BMI; however, 91.5% were at risk of unhealthy central fat distribution, and 70.3% demonstrated unhealthy lifestyle habits, with an average energy intake of 1471.83 kcal, below the recommended level. The nutritional status of the students was influenced by imbalanced dietary behaviors, indicating a need for nutritional interventions and education to enhance awareness of nutritious food choices.